Guidelines for scope of work in corporate office building design. - Julião, Mariana Lopes (2018)
Project process\' hindrances over office architectural design production are common at civil construction sector, implying on schedule loss, reworks and higher costs. Many academic literature approaches to that hindrance resulted from failure in project process. Predominantly failures concern translating customer needs and expectations into design conditions. This research objectives to propose scope of work guidelines, securing customer satisfaction and avoiding unforeseen additional costs, reworks, schedule and project benefit loss. Additionally, for each guideline proposed, it is suggested an accountable for it (project manager, architect or client). The adopted methodology was the research and analysis of project methodologies from academic literatures, contenting responsibilities definitions and design criteria that should be considered on the approved scope of work. Furthermore, the creation and implementation of an interview plan with one Brazilian high concept corporative architecture firm and its three clients, in a way that it is possible to measure client\'s point of view over contracted project process. Results from the interviews identified scope definition and project process planning hindrances. Then, in comparison with academic literatures, main project and scope of work issues were identified and used as base to the scope of work development guidelines.